An X-ray diffraction study of deformation in h.c.p. rare-earth metals - Gupta R.K.; Anantharaman T.R. (My University, 2025)
A detailed analysis has been made of X-ray line broadening in deformed filings of gadolinium, terbium, dysprosium, holmium and erbium. Values of small domain size, microstrains within these domains and stacking fault probabilities have been arrived at, utilising Fourier as well as integral breadth analysis. Gadolinium is characterised by a fault probability of ~0.007, but there is no evidence for faulting in other metals. The results of Fourier and integral breadth analysis of several X-ray reflections in each case conform to the elastic isotropy of these rare-earth metals. © 1971.